PENGARUH INTENSITAS MENONTON FILM ANIMASI ADIT SOPO JARWO TERHADAP INTERAKSI SOSIAL ANAK SEKOLAH DASAR - Dody Ginanjar; Amiruddin Saleh (Jurnal Komunikasi Pembangunan, 2020)
Television is one of the mass media that is very popular and has a tendency to be able to influence and meet the needs of its audience, including children. One of the television shows good packed for children is the animated film, which titled Adit Sopo Jarwo. The objectives of the study were: (1) to describe watching intensity of the animated film Adit Sopo Jarwo and children's social interaction in Al Azhar Elementary School Depok City and Cipayung Eementary School Depok City, West Java, (2) to analyze intensity effect of watching the animated film Adit Sopo Jarwo on children's social interactio in Al Azhar 46 Islamic Elementary School, Depok City, and Cipayung Elementary School Depok City, West Java. Research with a quantitative approach to survey research desgin. The number of respondents in the study were 75 respondents. Slovin formula was applied for sampling technique and ordinal logistic regression test was applied for data analysis. The results showed that: (1) the intensity decription of watching Adit Sopo Jarwo and children's social interactions in both schools had different values. Students in SD Cipayung having a high watching intensity compared to Al Azhar Islamic Elementary School. Child social interaction in both schools shows a positive direction by establishing unity and increasing solidarity among group members. (2) the intensity of watching Adit Sopo Jarwo affected children's social interaction.